The use of protective structures to reduce tunnelling induced damage to buildings - Song, Geyang (2019)
In urban areas, due to the limited underground space, tunnels are being built close to or underneath existing buried foundations. As a result, it is essential to understand the effect of tunnelling on nearby structures and buried foundations. Tunnel-structure interaction problems have been widely investigated via numerical and physical modelling as well as with field monitoring. However, the use of protective measures, such as protective walls, to reduce the effect of tunnelling on structures have received much less research attention. Protective measures are often very costly and designed in an overly conservative way. A better understanding of tunnel, soil, piled structure and protective wall interaction (TSPPWI) problems would enable more efficient and cost-effective protective measures to be adopted.